2015
DOI: 10.1007/s11892-015-0660-z
|View full text |Cite
|
Sign up to set email alerts
|

The Detection and Management of Diabetes Distress in People With Type 1 Diabetes

Abstract: Diabetes distress (DD) represents a significant clinical burden in which levels of DD are related to both HbA1c and some self-management behaviours. DD is related to, but different from, depression.Differences in DD experienced in people with type 1 and type 2 have been observed. Commonly measured by the Problem Areas in Diabetes Scale and the Diabetes Distress Scale, rates of elevated DD in research study participants range 20-30%. Risk factors for elevated DD in type 1 are a longer duration of diabetes, seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
123
0
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 123 publications
(145 citation statements)
references
References 79 publications
(41 reference statements)
8
123
0
14
Order By: Relevance
“…Data on prevalence of anxiety and depression came from Mexico; however, the referent for prevalence of distress came mainly from the United States, since these data are not available for Mexican population. At the same time, prevalence of affective disorders (anxiety and depression) found in the present study is similar to the figures reported in similar studies (Fisher et al 2012;Sturt, Dennick, Due-Christensen & McCarthy, 2015;Fisher, Glasgow & Strycker, 2010). In our study, distress in diabetic patients was associated with poor adherence to medication and lack of regular physical exercise.…”
Section: Discussionsupporting
confidence: 92%
“…Data on prevalence of anxiety and depression came from Mexico; however, the referent for prevalence of distress came mainly from the United States, since these data are not available for Mexican population. At the same time, prevalence of affective disorders (anxiety and depression) found in the present study is similar to the figures reported in similar studies (Fisher et al 2012;Sturt, Dennick, Due-Christensen & McCarthy, 2015;Fisher, Glasgow & Strycker, 2010). In our study, distress in diabetic patients was associated with poor adherence to medication and lack of regular physical exercise.…”
Section: Discussionsupporting
confidence: 92%
“…Around one quarter of UK adults with diabetes experience elevated, or severe, DD at any given time (Dennick et al, 2016;Sturt, Dennick, Due-Christensen, & McCarthy, 2015). Similar rates are reported elsewhere in Europe (Stoop et al, 2014), Australia (Speight et al, 2011) and the USA (Fisher, Skaff, et al, 2008).…”
Section: Introductionsupporting
confidence: 66%
“…They included: The Problems Areas in Diabetes (PAID) (20 items) with scores ≥ 40 representing severe diabetes-related distress (12,13), and a score ≥ 30 representing significant diabetes-related distress; The Kessler 10 (K10; 10 items) assessing psychological distress, focusing on depression and anxiety symptoms, ow levels of distress (10)(11)(12)(13)(14)(15), moderate (16)(17)(18)(19)(20)(21), high level (22)(23)(24)(25)(26)(27)(28)(29) and very high are defined (14,15); The WHO-5 Well-being Index (5 items) assessing quality of life, with scores ≤ 13 indicative of low well-being, and scores < 8 indicative of depression (16,17) (22), (23) were compared to USA normative data (non-diabetic), and 4 items assessed financial concerns.…”
Section: Methodsmentioning
confidence: 99%